THE EFFECTS OF GYMNASTICS TRAINING ON STATIC BALANCE AMONG CHILDREN AGED 4 TO 8 - TANASĂ R.A; DUMITRU I.M; BUDACĂ M.V (Editura Universitatii Transilvania din Brasov, 2020)
Balance, along with the other motor skills, have an important role in the execution of sports habits. The purpose of the study was to design and apply a system of actuation means improving the static balance of gymnasts. The study was carried out on a sample of 35 children, aged from 4 to 8, while the tests used were the following: the Flamingo Test, the Unipodal Test and The Bruininks-Oseretsky Test. After interpreting the results, using the ANOVA statistical analysis test, the following values were obtained: the Flamingo test p<0.0001, on the right leg -3.714 and of the left leg -3.829; the unipodal test p<0.0001, on the right leg -4.086, on the left leg -3.829; the Bruininks-Oseretsky Test p<0.0001, on the right leg -3.457 and on the left leg -3.657. Considering the results obtained, it may be stated that the actuation means used in the study were efficient and they led to an improvement of the balance capacity.